Respuesta :

Answer:

Step-by-step explanation:

(a). ( f + g )( x )

( x³ - [tex]\frac{1}{2}[/tex] x² + x ) + ( x² - [tex]\frac{1}{4}[/tex] x - 4 ) =

x³ + ( - [tex]\frac{1}{2}[/tex] + 1 ) x² + ( 1 - [tex]\frac{1}{4}[/tex] ) x - 4 =

x³ + [tex]\frac{1}{2}[/tex] x² + [tex]\frac{3}{4}[/tex] x - 4

(b). ( f - g )( x )

( x³ - [tex]\frac{1}{2}[/tex] x² + x ) - ( x² - [tex]\frac{1}{4}[/tex] x - 4 ) =

x³ - [tex]\frac{1}{2}[/tex] x² + x - x² + [tex]\frac{1}{4}[/tex] x + 4 =

x³ + ( - [tex]\frac{1}{2}[/tex] - 1 ) x² + ( 1 + [tex]\frac{1}{4}[/tex] ) x + 4 =

x³ - [tex]\frac{3}{2}[/tex] x² + [tex]\frac{5}{4}[/tex] x + 4

(c). ( f + g )( 2 )

2³ + [tex]\frac{1}{2}[/tex] ( 2 )² + [tex]\frac{3}{4}[/tex] ( 2 ) - 4 = 8 + 2 + [tex]\frac{3}{2}[/tex] - 4 = [tex]7\frac{1}{2}[/tex]

(d). ( f - g )( - 3 )

( - 3 )³ - [tex]\frac{3}{2}[/tex] ( - 3 )² + [tex]\frac{5}{4}[/tex] ( - 3 ) + 4 = - 27 - [tex]\frac{27}{2}[/tex] - [tex]\frac{15}{4}[/tex] + 4 = - 23 - [tex]\frac{69}{4}[/tex] = - [tex]40\frac{1}{4}[/tex]